Assessment of the new Next Generation Sequencing (NGS) tools to identify genes associated with tolerance to water deficit in sugarcane - John Jaime Riascos Arcos; Héctor Fabio Espitia Navarro; Jershon López Gerena (Acta Agronómica)
The aim of this research was to evaluate the performance of the new Next Generation Sequencing (NGS) technologies in comparative transcriptomics experiments, aiming to identify genes associated with tolerance mechanisms to abiotic stress such water deficit or flooding in sugarcane. Despite being widely used in most of current comparative transcriptomics studies, it is important to test the utility of NGS technologies in species such as sugarcane considering its genome complexity and the fact that there is no reference genome, which could be of use in this type of studies. For this purpose, in this investigation, varieties tolerant and susceptible to drought or flooding were selected and independently subjected to stress (medium or severe levels) due to drought or flooding, in order to induce the production of mRNAs of interest. For each of these, leaves were collected and cDNA libraries produced (a total of 12). Each library was sequenced using NGS methodologies (Illumina-RNA-Seq) and data were analyzed using specialized bioinformatics software. Among the genes that were observed as differentially expressed it was possible to identify orthologs of those previously associated with tolerance for the traits of interest. Also, it was possible to detect differences in expression levels of highly similar transcripts. Our results provide evidence that support the use of NGS technologies in transcriptomics studies in genetically complex species such as sugarcane.